VISITORS’ PERCEPTION TOWARDS INFRASTRUCTURE, ECOLOGICAL QUALITY AND THE WILLINGNESS TO PAY IN THE REGION OF ANECC IN AEK NAULI - Wanda Kuswanda (Inovasi, 2021)
The purpose of this study was to determine visitor perceptions of facilities, ecological quality and willingness to pay at ANECC (Aek Nauli Elephant Conservation Camp), Aek Nauli Special Purpose Areas. The study was conducted in September to November 2018. This research was conducted using a qualitative approach. Data collected in this study came from primary data (interviews with respondents namely ANECC visitors). The selection of respondents was carried out by purposive random sampling and data analysis techniques used in this study were qualitative descriptive. The visitor's perception of the facilities at ANECC is quite good although there are still a few things that need to be improved. The majority of visitors come to ANECC to see elephants as much as 72%, enjoy the natural atmosphere as much as 27% and beautiful scenery as much as 23%. Visitors agree (76%) if admission is charged and around 43% are willing to pay IDR 5,000. Visitors are willing to pay to help elephant conservation by 92%. If there is an attraction to ride an elephant, the majority of visitors are willing to pay IDR 30,000 – IDR 39,000, - for 10-15 minutes outside the entry ticket. Willingness to pay the majority of visitors to see the elephant attraction show IDR 10,000 - IDR 15,000 - although 33% of respondents are willing to pay IDR 20,000 - IDR 25,000. Visitors also recommend ANECC management to improve facilities, maintain environmental quality to increase the attractiveness of visitors and PNBP sources because the WTP value of visitors is quite good.